Survey of Well Waters Located in the Arid Zone of Rajasthan and their Influence on Soil Properties with Special Reference to Salinity - Singh, K.S.; Mahnot, S.C. (Journal of Soil and Water Conservation, 2022)
With increasing user of irrigation water for good crop production; it has become necessary to have a knowledge of the quality of waters so as to adopt proper soil and water management practices in order to sustain high yield. The areas under observation, in the present investigation lie in the arid and semi-arid regions of Rajasthan. The only source of irriga- tion is the supply of water from wells of varying depths depending upon the ground water level. The replenishment of these wells depend on the annual monsoon rain. The waters of the areas are greatly varying in quality and fall in all classes of E.C. and S.A.R. based on U.S.S.L. classification Richards, 1954 ).